Mismatch Negativity Recording in Children With Duchenne Muscular Dystrophy: A Preliminary Study Integrating Neurophysiological and Neuropsychological Results. (November 2016) - Filippini, Melissa; Guerra, Angelo; Negosanti, Alessandra; Santi, Sara; Sarajlija, Jasenka; Musti, Muriel Assunta; Gobbi, Giuseppe; Lassonde, Maryse; Pini, Antonella
Many studies on Duchenne muscular dystrophy children support the hypothesis of a specific neuropsychological phenotype affecting mostly phonological skills. This prospective study aimed to shed light on the role of phonological abilities. Fourteen Duchenne muscular dystrophy children and 7 healthy children underwent mismatch negativity. Moreover, verbal intelligence, visuospatial attention, immediate verbal memory, working memory, grammar, vocabulary, visuomotor skills, reading, text comprehension, writing, and arithmetic were tested in Duchenne muscular dystrophy children. No significant difference between control and Duchenne muscular dystrophy children was found neither for mismatch negativity amplitude ( P = .191 and .116, respectively) nor for latency ( P = .135). Eight (57.14%) patients showed an impairment of immediate verbal memory and of visuomotor skills, 7 (63.64%) patients had a deficit in writing and arithmetic skills, even with a mean normal intelligence quotient. Taken together, the results put in evidence a heterogeneous neuropsychological profile not explainable on the basis of a phonological deficit.